2020
DOI: 10.1002/cam4.2846
|View full text |Cite
|
Sign up to set email alerts
|

Detection of AXL expression in circulating tumor cells of lung cancer patients using an automated microcavity array system

Abstract: Noninvasive diagnostics using circulating tumor cells (CTCs) are expected to be useful for decision making in precision cancer therapy. AXL, a receptor tyrosine kinase is associated with tumor progression, epithelial‐to‐mesenchymal transition (EMT), and drug resistance, and is a potential therapeutic target. However, the epithelial markers generally used for CTC detection may be not enough to detect AXL‐expressing CTCs due to EMT. Here, we evaluated the detection of AXL‐expressing CTCs using the mesenchymal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…A pivotal aspect of CTC analysis resides on the possibility to perform successive liquid biopsies to monitor the progression of the disease and to assess treatment efficacy. Importantly, the emergence of EMT-shifted CTC phenotypes after one or several lines of treatment was found to correlate with drug resistance in several studies [52,104,112,121,124,179,360]. This finding is in agreement with a large amount of experimental data demonstrating an enhanced ability of EMT-shifted cells to resist most existing therapeutic options (chemo-radio-resistance, and resistance to existing targeted therapies) [81,[162][163][164][165][166].…”
Section: Emt + Ctcs In Therapy Managementsupporting
confidence: 77%
See 4 more Smart Citations
“…A pivotal aspect of CTC analysis resides on the possibility to perform successive liquid biopsies to monitor the progression of the disease and to assess treatment efficacy. Importantly, the emergence of EMT-shifted CTC phenotypes after one or several lines of treatment was found to correlate with drug resistance in several studies [52,104,112,121,124,179,360]. This finding is in agreement with a large amount of experimental data demonstrating an enhanced ability of EMT-shifted cells to resist most existing therapeutic options (chemo-radio-resistance, and resistance to existing targeted therapies) [81,[162][163][164][165][166].…”
Section: Emt + Ctcs In Therapy Managementsupporting
confidence: 77%
“…A recent study of CTCs isolated from breast cancer patients and mouse models, reported that the binding sites for CSC transcription factors such as OCT4, SOX2, or NANOG, are hypomethylated in CTC clusters compared with isolated CTCs [49]. Other data collected from human samples also emphasize the presence of hybrid E/M phenotypes in heterogeneous CTC clusters, particularly in lung cancers [51,52,109,190]. Very elegantly, a study by Yu and coworkers identified cells expressing both epithelial (such as EpCAM or cytokeratins) and mesenchymal markers (including fibronectin, N-cadherin or PAI-1) in isolated CTCs but also in CTC clusters from breast cancer patients [179].…”
Section: Traveling In Clustersmentioning
confidence: 98%
See 3 more Smart Citations